2012
DOI: 10.1371/journal.pgen.1002578
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Positive Selection on a Number of MicroRNA Regulatory Interactions during Recent Human Evolution

Abstract: MicroRNA (miRNA)–mediated gene regulation is of critical functional importance in animals and is thought to be largely constrained during evolution. However, little is known regarding evolutionary changes of the miRNA network and their role in human evolution. Here we show that a number of miRNA binding sites display high levels of population differentiation in humans and thus are likely targets of local adaptation. In a subset we demonstrate that allelic differences modulate miRNA regulation in mammalian cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 58 publications
5
64
1
Order By: Relevance
“…For c-e, two-sided unpaired t-tests with Welch's correction were performed. Source data are available in Supplementary Table 8. miR-155-dependent mRNA decay of TYRP1-A, limiting TYRP1-A mRNA turnover 27,30 . Third, non-canonical miR-16-binding sites sequester miR-16.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For c-e, two-sided unpaired t-tests with Welch's correction were performed. Source data are available in Supplementary Table 8. miR-155-dependent mRNA decay of TYRP1-A, limiting TYRP1-A mRNA turnover 27,30 . Third, non-canonical miR-16-binding sites sequester miR-16.…”
Section: Discussionmentioning
confidence: 99%
“…The highly expressed miR-211 was not co-purified, nor was miR-330, whose expression level was intermediate between those of miR-16 and miR-155 (Supplementary Table 2). In addition, miR-155 had already been shown to interact with the TYRP1 3 UTR, giving robustness to this approach 30 . TargetScan, a computational method predicting miRNA targets 4 according to perfect sequence match between an miRNA seed region and its targets, failed to detect MRE-16 on TYRP1.…”
Section: Tyrp1 Mrna Sequesters Mir-16mentioning
confidence: 99%
See 1 more Smart Citation
“…miRNA regulation has a significant impact on the evolution of metazoan 3 ′ UTRs (Farh et al 2005;Stark et al 2005;Bartel 2009). Although a large number of mutations in the 3 ′ UTRs potentially create or destroy miRNA target sites (Chen and Rajewsky 2006;Clop et al 2006;Saunders et al 2007;Sethupathy and Collins 2008;Chen et al 2009;Gong et al 2012;Li et al 2012;Lu and Clark 2012;Moszynśka et al 2017), only a small fraction of the target sites are evolutionarily conserved and likely to be functional (Enright et al 2003;Stark et al 2003;John et al 2004;Rajewsky and Socci 2004;Brennecke et al 2005;Grün et al 2005;Lewis et al 2005;Bartel 2009;Friedman et al 2009;). Previous studies suggest that the functional development of miRNA target sites might be evolutionarily dynamic, with frequent gains and losses of target sites during this evolutionary process (Xu et al 2013;Liu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have shown that miRNAs are involved in many important biological processes [15,16], like cell differentiation [17], proliferation [18], signal transduction [19], viral infection [20], and so on. Therefore, it is easy to find that miRNAs have close relationship with various human complex diseases [12,[21][22][23][24][25][26]. For example, researchers found that mir-433 is upregulated in gastric carcinoma by regulating the expression of GRB2, which is a known tumour-associated protein [27].…”
Section: Introductionmentioning
confidence: 99%